1986
DOI: 10.2135/cropsci1986.0011183x002600030033x
|View full text |Cite
|
Sign up to set email alerts
|

Planting Patterns and Soybean Yields1

Abstract: No satisfactory explanation for the effect of planting patterns on soybean [Glyclne max (L.) Merr.] seed yields under favorable growing conditions has been proposed. The purpose of this paper is to suggest two postulates that together explain soybean yield response to various planting patterns. They are: (1) seed yields continue increase with plant density to a limit that is well above that needed for almost complete light interception, and (2) yield is directly related to vegetative plant weight, all other co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 0 publications
6
71
1
3
Order By: Relevance
“…Para essa região, a densidade de semeadura de 12 a 36 plantas m -2 não resultou em diferenças de RG, mas alterou as características morfoagronômicas da planta (EP, DH, NH, NV e GP). Esses resultados sugerem que existe uma fase IV, em que o aumento da densidade de plantas não altera o rendimento de grãos, diferentemente da fase III (aumento da densidade de plantas aumenta o rendimento de grãos), descrita por Duncan (1986). A alteração da Relação entre densidade de plantas e genótipos de soja ... (Oz, 2008).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Para essa região, a densidade de semeadura de 12 a 36 plantas m -2 não resultou em diferenças de RG, mas alterou as características morfoagronômicas da planta (EP, DH, NH, NV e GP). Esses resultados sugerem que existe uma fase IV, em que o aumento da densidade de plantas não altera o rendimento de grãos, diferentemente da fase III (aumento da densidade de plantas aumenta o rendimento de grãos), descrita por Duncan (1986). A alteração da Relação entre densidade de plantas e genótipos de soja ... (Oz, 2008).…”
Section: Resultsunclassified
“…Relação entre densidade de plantas e genótipos de soja ... Duncan (1986), existem três fases de resposta do rendimento de grãos de soja em função da densidade de plantas: fase I -a densidade de plantas é muito baixa (1 a 2 plantas m -2 ), não se verifica competição entre plantas e o rendimento de grãos por planta é máximo; fase II -a planta começa a competir pelos recursos ambientais com a outra (2 a 12 plantas m -2 ); e fase III -caracterizada pela relação positiva entre o aumento na densidade de plantas e o aumento do rendimento de grãos por área (maior que 12 plantas m -2 ), sendo o limite desta fase até interceptação da radiação fotossinteticamente ativa de 95% para se alcançar o máximo rendimento de grão por área. Esta última fase seria a densidade de plantas a ser alcançada nesta pesquisa.…”
Section: Introductionunclassified
“…The dense planting increases the competition among plants from the early stage and the risk of excessive growth which results in lodging. On condition that the planting density is equal, narrow row-spacing decrease the competition with plants during the earlier growth stage than wide row-spacing, and result in rapid leaf area expansion, higher crop growth rate and higher seed yield due to the development of branches, increase in the node number and pod number per node (Cooper 1977, Costa et al 1980, Duncan 1986, Miura and Gemma 1986, Miura et al 1987, Board et al 1990a, 1990b, Bullock et al 1998, Ikeda 2000. However, narrow row-spacing did not increase the yield (Beatty et al 1982, Nakano 1989) and has been reported to even decrease the yield (Cooper and Nave 1974).…”
Section: Introductionmentioning
confidence: 99%
“…5). Since pod development on soybean is an indeterminate process, the older pods developed and filled properly at an early stage of plant development, when competition between plants was not severe at high planting density (Duncan, 1986). Pod weight of the uppermost stratum was reduced significantly because of intense competition between plants at later stage of development.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the response of soybean genotypes to planting density has attracted considerable attention (Egli, 1988;Bullock et al, 1998;Gan et al, 2002). The spatial distribution of soybean plants has been reported to influence growth and yield responses (Duncan, 1986;Robinson and Wilcox, 1998) by affecting canopy photosynthesis and light interception capacities (Wells, 1991;Board, 2000;Singer, 2001). Close spacing enhances light interception.…”
Section: Introductionmentioning
confidence: 99%